PROBLEM GAME AND EXPERIMENT PHILOSOPHICAL THEORY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In the mentioned article of the author, the problem of play in the experience ofphilosophical theory is considered, besides, as mentioned in it, play is much bigger than man. Inits original form, it was formed in the universe of beings capable of moving in space. The gamewas necessary for young animals as a means of strengthening the body, mastering the methodsof struggle for life, leaning on the experience of existence accumulated in the endless exchangeof previous generations, and enjoying it. Here the activity is instinctive. A completely differentmethod of activity appears in human society - activity based on a conscious goal. Purposiveness,which naturally arises in the processes of physical survival, beginning with finding food, graduallyspreads to more complex spheres of human activity. In it, the initial uncertain gaming impulses aresubdued.
Keywords: game phenomenon, “pure game”, active approach, freedom of choice, philosophy of culture, organism, society, struggle, practical sphere.